PENGEMBANGAN ALAT PERMAINAN EDUKATIF (APE) ULAR TANGGA UNTUK MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK USIA 4-5 TAHUN - Fitri Rismadani; Defni Satria; Rita Kurnia (UIR PRESS, 2022)
This study aims to determine the development and feasibility of the snake ladder educational game tool (APE) to improve the gross motor skills of children aged 4-5 years. The research method used is Research and Development (RND), which produces a product and can test the effectiveness of the product. The data analysis technique used by the researcher in this study is a quantitative descriptive analysis technique. Data analysis for product feasibility uses the assessment of the results obtained from learning media experts and material experts in the form of a questionnaire instrument (questionnaire). The resulting product development in the form of an educational game tool (APE) snake ladder made of banner printing material with a size of 2.4 x 3 meters is used as a learning medium to improve gross motor skills of children aged 4-5 years. The validation results obtained in the development of the snake and ladder educational game tool (APE) are very satisfying. The results of material validation are in the